POLYMORPHISM OF VASCULAR ENDOTHELIAL GROWTH FACTOR REGIO PROMOTER C(-634)G AS A RISK FACTOR OF BALINESE TYPE-2 DIABETIC RETINOPATHY - Mas-Putrawati, A. A.; Bakta, M.; Suastika, K.; Muhiddin, H. S. Habiba; Niti Susila, N. K. (BALI MEDICAL JOURNAL; Vol 4 No 2 (2015), 2015)
Background: Diabetic retinopathy (DR) is one of the complications on diabetic mellitus (DM) patient as a micro vascular retina disorder which caused by a long term of hyperglycemia. This is one of the blindness causes in the world. This research aims to find out Polymorphism of VEGFC(-634)G gene as a risk factor of DR on the Balinese with DM type-2 (DMT2). Method: This study is applying two designs, analytical cross sectional and case control. The case is DMT2 patient with DR(+), DMT2 without DR as control. The sequencing technique was performed to evaluate polymorphism and plasma VEGF levels were determined by ELISA. Results: Cross sectional study (hospital based) came out with quite high number of DR, 57 people of 97 study samples. This study shows the existence of genetic variation on Gen VEGF C(-634)G, with most often genotype of CG (51.5%). Polymorphism C(-634)G as the risk factor of DR (OR=1.815 CI-95%= 1.077-3.057, p=0.025), and high level of VEGF were also significant (QR=3.75 , CI-95% 1.34-10.20, p=0.008). VEGF level with genotype of CG, CC and GG, not found any difference (p=0.245). Logistic regression shows that the most influential variable as the risk factor of DR is VEGF level (p= 0.007), polymorphism gen VEGF C(-634)G (p=0.022) and systolic blood pressure (p=0.023). Conclusions: Polymorphism of VEGF C(-634)G gene and high level of VEGF as the risk factor of DR, and can be used as a reference in handling early stage of DR patient to prevent blindness.
Keywords: diabetic mellitus, retinopathy, polymorphism, VEGF levels.